2011
DOI: 10.1088/0964-1726/20/8/085004
|View full text |Cite
|
Sign up to set email alerts
|

A geometric parameter study of piezoelectric coverage on a rectangular cantilever energy harvester

Abstract: This paper proposes a versatile model for optimizing the performance of a rectangular cantilever beam piezoelectric energy harvester used to convert ambient vibrations into electrical energy. The developed model accounts for geometric changes to the natural frequencies, mode shapes and damping in the structure. This is achieved through the combination of finite element modelling and a distributed parameter electromechanical model, including load resistor and charging capacitor models. The model has the potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…Maximum power output can be obtained for a certain length of the transducer layer. Patel et al developed a comprehensive theoretical model for analysing piezoelectric cantilever beams with varying length and thickness of the piezoelectric layer [ 11 ]. These two parameters proved to be significant for increasing the output power.…”
Section: Introductionmentioning
confidence: 99%
“…Maximum power output can be obtained for a certain length of the transducer layer. Patel et al developed a comprehensive theoretical model for analysing piezoelectric cantilever beams with varying length and thickness of the piezoelectric layer [ 11 ]. These two parameters proved to be significant for increasing the output power.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al, experimented on a rectangular cantilever by applying constant acceleration at a weight of 2 g and concentrated on the control parameters, tip mass inertia and substrate thickness mainly [43].…”
Section: External Excitationmentioning
confidence: 99%
“…Several articles and significant research have been devoted to developing and understanding power-harvesting systems, with an emphasis on piezoelectric conversion to generate electricity from vibrations [4][5][6][7][8][9][10][11][12][13]. These studies demonstrated the feasibility of using piezoelectric materials as power sources.…”
Section: Introductionmentioning
confidence: 99%
“…The design comprises a multimode intermediate beam with a tip mass, called a dynamic magnifier. Patel et al [13] proposed a versatile model for optimising the performance of a rectangular cantilever beam piezoelectric energy harvester used to convert ambient vibrations into electrical energy. The developed model accounts for geometric changes to the natural frequencies, mode shapes, and damping in the structure.…”
Section: Introductionmentioning
confidence: 99%